What Factors Affecting Auditors’ Fraud Tendency Perception? Fraud Pentagon Theory Perspective - Fakhmi Zakaria; Suhita Whini Setyahuni (Equity: Jurnal Ekonomi, 2024)
This research aims to analyze the influence of the pentagon fraud theory, which consists of pressure, opportunity, rationalization, competence, and arrogance, on auditors' perceptions of fraud tendencies. The sample for this research is 153 auditors who work at the Regional Inspectorate of Central Java Province. This type of research is quantitative research. The data analysis technique uses Partial Least Square (PLS). Data was processed using SmartPLS software version 3.29. The results of this research are that pressure, opportunity and rationalization do not have a significant effect on the auditor's perception of fraud tendencies, while competence and arrogance have a significant effect on the auditor's perception of fraud tendencies.